Figurative language in ritual verse: Linguistic and cultural perspective on Syair Manoe Pucok - Nofiana Nofiana; Nurjannah Nurjannah; Hayatun Rahmi; Jihan Almira (Universitas Muhammadiyah Malang, 2026)
Syair Manoe Pucok is a key part of the Manoe Pucok purification ceremony. It serves both as a form of art and as an expression of parental care, offering moral lessons to the younger generation. However, despite its importance, the linguistic and stylistic aspects of this syair have received little scholarly attention. This study, therefore, aims to analyze the types of figurative language used in Syair Manoe Pucok and to interpret their cultural and pedagogical meanings. Employing a mixed-method approach, the research integrates linguistic-stylistic analysis with ethnographic interpretation. Data were collected from authentic syair lyrics performed by cultural practitioners in Aceh Barat Daya, supported by semi-structured interviews. The procedures included transcription, translation, coding of figurative expressions, stylistic analysis of poetic structures, and cultural interpretation validated through triangulation. The findings reveal four types of figurative language: symbolism (65%), metaphor (20%), hyperbole (10%), and personification (5%), with symbolism dominating the discourse. These stylistic devices function as more than decorative language; they embody purification, blessings, and parental counsel, reinforcing communal identity and moral values. In conclusion, Syair Manoe Pucok emerges as both an aesthetic expression and an educational medium, sustaining cultural continuity while strengthening spiritual and emotional bonds within Acehnese society.